ETIKA PROFESI GURU PENDIDIKAN ANAK USIA DINI DI KECAMATAN PADANG TIMUR KOTA PADANG - Wandi, Zherly Nadia; Nurhafizah, Nurhafizah (Laboratorium Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Riau, 2019)
This study aims to determine the professional ethics of early childhood education teachers in kindergartens in Padang Timur Subdistrict, Padang City. This study uses descriptive methods that are analytical. Respondents involved included teachers, and principals. For the target population in this study were kindergarten teachers in Padang Timur District, Padang City in 5 Kindergarten Institutions with 41 samples. Data collection is done through observation or observation, interviews and documentation. The results of the study indicate that in early childhood education teacher ethics, based on Republic of Indonesia Law Number 14 of 2005 concerning Teachers and Lecturers also Decision of the XXI Congress of the Republic of Indonesia Teacher Association Number: Vi / Congress / Xxi / Pgri / 2013 concerning Teacher Ethics Code Indonesia with its research focus, namely 1) The obligation of teachers to students; 2) Obligations of teachers to parents or guardians of students; 3) The teacher's obligation to colleagues shows that there are indeed differences that occur in the field, such as one of the teacher's ethics towards parents, teachers must be able to maintain good communication with parents. So it can be concluded that the ethical analysis of early childhood education teachers in Padang Timur Subdistrict, Padang City, is in accordance with the decisions or policies set, although there are several points when carried out in the field does not run optimally. So it is necessary to collaborate with teachers and principals and parents / guardians of students in providing educational services to children so that the teacher can also improve competence and ethics or good behavior in learning.